If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(6)+3y=6-6-6
We move all terms to the left:
(6)+3y-(6-6-6)=0
We add all the numbers together, and all the variables
3y+6-(-6)=0
We add all the numbers together, and all the variables
3y+12=0
We move all terms containing y to the left, all other terms to the right
3y=-12
y=-12/3
y=-4
| x=11+29 | | 106=(2y+34) | | -1/2(4w+6)=1/2(9-3w) | | 6+m/3=8 | | 12+2x=3(−x+8)−27 | | 106=(2y4+34) | | 106=(2x+34) | | -5x-36=10 | | 07.a+2=23 | | -12n-5=-65 | | 12x-14=22+0x | | 15x+2=8x-28 | | 0.3(6x-9)=4.5 | | n−575=24 | | x-4=2x-16 | | 75.25+20=4.25x | | 17-p=40 | | (14x+7)=(20x+15) | | 14d=280 | | 171/2x+40=88 | | z/3+5=26 | | x-72=-8x+9 | | d=2053 | | 15x+12=154 | | -6t+13=16 | | f/24=-23 | | 28-x=2x+32 | | -6x+2=-10* | | −3x+4+2x=15 | | -2(y-9)=2y+6 | | f24=–23 | | 2x–3=x+(-1) |